Effects of prolonged oxytetracycline supplementation on freshwater stinging catfish (Heteropneustes fossilis): a multi-biomarker approach - Pushpa Choudhary; Saisweta P. Naik; Sameer Ranjan Sahoo; Rakesh Das; Satya Narayan Sahoo; Satyen Kumar Panda; Thangapalam Jawahar Abraham; Prasanna Kumar Patil; Priyabrat Swain; Sudhansu Sekhar Mishra (Frontiers in Immunology)
BackgroundAquaculture systems that sporadically depend on antibiotics can contribute to the development of adverse effects on the fish, microbial flora and the environment. This study sought to investigate the impacts of extended oxytetracycline supplementation on the freshwater stinging catfish Heteropneustes fossilis through a multi-biomarker approach.MethodsA total of 300 H. fossilis (20 ± 0.5 g) were placed in fibreglass-reinforced plastic tanks. The experimental fish were administered oxytetracycline hydrochloride (OTC) at varying doses, viz., 80 mg/kg fish biomass/day (1x), 240 mg (3x), 400 mg (5x), and 800 mg (10x) for 30 consecutive days. The study also included a control group that did not receive OTC.ResultsOTC was effective against Aeromonas hydrophila, Pseudomonas putida, and Plesiomonas shigelloides, with minimum inhibitory concentrations ranging between 0.5 and 8.0 µg/mL. The OTC supplementation retarded the growth of fish. The respiratory burst activity, myeloperoxidase, and lysozyme increased significantly in the 1x group until day 20. This group showed an increase in serum albumin, whereas other OTC groups exhibited elevated levels of liver functional enzymes, including alanine transaminase, aspartate aminotransferase, and alkaline phosphatase. In addition, OTC groups exhibited increased levels of antioxidant enzymes. The magnitude of the increase was dose- and time-dependent. The liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) study signified a dose-dependent increase in OTC residues in the muscle. After a 10-day discontinuation of OTC, the tissue level retention of residues was minimal in the muscle, specifically in the 1x group compared to other groups. Significant histological alterations were noted in the liver tissues of the 5x and 10x groups, possibly due to oxidative stress and residue accretion.ConclusionThe therapeutic dose of 80 mg/kg biomass/day was safe and tolerated well by H. fossilis, and may be used for sustainable catfish farming practices.